Perceptions of a COVID-19 education public service announcement in Nunukan Regency, North Kalimantan: a qualitative study - Tiara Putri Leksono; Avinindita Nura Lestari; Reyfal Khaidar; Yuga Putri Pramesti; Syarmila Sari; Lutfan Lazuardi (Journal of Community Empowerment for Health, 2020)
Indigenous populations experience a risk of socio-economic marginalization in health emergency, including COVID-19. Public service announcements (PSA) are promotional materials that address problems in an attempt to increase public awareness. North Kalimantan is one of the frontier, outermost, and least developed regions in Indonesia with 11 regional languages spoken. One of the districts with inadequate human resources in the area is Nunukan regency. The present study sought to understand how one group of people in Nunukan Regency reactions, interests, and impressions with the COVID-19 information found in Bugis and Toraja version of audio PSAs released by Health Empowerment and Education Project (HEUProject). The study belongs to qualitative research and used purposive sampling with seven participants from two sub-district in Nunukan Regency. The data is analyzed qualitative-thematically which is further interpreted and presented  in the form of a description. Additionally, to see the variety of participants’ answers information transmission through PSAs, we analyzed the data using Tableau software 2020 version and presented the relative frequency of words with visual infographic. The study findings of the participants' immediate reactions were following the advice on the PSAs audio, for instance to keep the physical distance and washing their hands frequently. The most participants in this study have the willingness to hear, to understand, and also feel interested with the useful content in audio format that apparently improves their awareness of COVID-19 information. Overall, it is immediately apparent that the language, transmission of message, and information found in the HEUProject’s COVID-19 educational PSA were understood and engaged by participants in a way that it reflects on the pandemic situation. Our study supports the national usage of disease prevention with this type of media approach that could be used in public places in the future that may minimize the language divide.